Pengaruh Model Pembelajaran Contextual Teaching and Learning terhadap Hasil Belajar Siswa pada Matematika materi Bangun Ruang - Dian Wahyuni; Mufidah Mufidah; Akina Akina; Nuraini Nuraini (Jurnal Pendidikan Sultan Agung, 2023)
This study aims to determine the effect of using the Contextual Teaching and Learning (CTL) learning model on student learning outcomes in mathematics for class V SD Inpres Lawua 1. This research is an experimental study. The research design used was a Quasi Experimental Design with a control group pre-test post-test design. This study used two classes, namely the experimental class and the control class. The sample of this research was the fifth grade students of SD Inpres Lawua 1, which consisted of 25 students. The experimental class consisted of 13 people and the control class consisted of 12 people. Data collection was carried out using an instrument in the form of multiple choice questions, data analysis using the Paired Sample T-test and prerequisite tests, namely the normality test and homogeneity test with the help of the SPSS version 16 program. Based on the results of the t test using the Paire Sample T-test, the sig. (2-tailed) of 0.000 < 0.05. Then the hypothesis Ha is accepted and Ho is rejected, meaning that the CTL learning model on geometric material influences the learning outcomes of fifth grade students at SD Inpres Lawua 1.